Comparative Profiling of N-Glycans Isolated from Serum Samples of Ovarian Cancer Patients and Analyzed by Microchip Electrophoresis - Mitra, Indranil (2013)
Ovarian cancer is the fifth leading cause of cancer-related mortalities for women in the United States and the most lethal gynecological cancer. Aberrant glycosylation has been linked to several human diseases, including ovarian cancer, and accurate measurement of changes in glycosylation may provide relevant diagnostic and prognostic information. In this work, we used microchip electrophoresis coupled with laser-induced fluorescence detection to determine quantitative differences among the N-glycan profiles of control individuals and late-stage recurrent ovarian cancer patients prior to and after an experimental drug treatment that combined docetaxel and imatinib mesylate. N-Glycans were enzymatically released from 5-μL aliquots of serum samples, labeled with the anionic fluorescent tag, 8-aminopyrene-1,3,6-trisulfonic acid, and analyzed on microfluidic devices. A 22-cm long separation channel, operated at 1250 V/cm, generated analysis times less than 100 s, separation efficiencies up to 8 × 10(5) plates (3.6 × 10(6) plates/m), and migration time reproducibilities better than 0.1% relative standard deviation after peak alignment. Principal component analysis (PCA) and analysis of variance (ANOVA) tests showed significant differences between the control and both pre- and post-treatment cancer samples and subtle differences between the pre- and post-treatment cancer samples. Area-under-the curve (AUC) values from receiver operating characteristics (ROC) tests were used to evaluate the diagnostic merit of N-glycan peaks, and specific N-glycan peaks used in combination provided AUCs > 0.90 (highly accurate test) when the control and pre-treatment cancer samples and control and post-treatment samples were compared.